High pt utilization electrodes for polymer electrolyte membrane fuel cells by dispersing pt particles formed by a preprecipitation method on carbon ``polished'' with polypyrrole - Unni, SreeKuttan M.; Dhavale, Vishal M.; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (Journal of Physical Chemistry C, 2010)
Pt utilization on carbon black (CB) has been significantly improved by initially utilizing polypyrrole (PPy) as a moiety to ``polish'' the carbon surface and subsequently by dispersing Pt particles formed by a preprecipitation process to minimize their migration into the geometrically restricted areas of the carbon surface. This process strategy has helped to significantly extend the triple-phase boundary as a greater number of Pt particles comes in direct contact with Nafion, leading to a substantial improvement in the overall catalyst utilization. Preliminary analyses such as IR, thermogravimetric analysis, and N(2) sorption confirmed the presence of PPy on the surface. Approximately 50% reduction in the surface area of CB after the controlled in situ polymerization of pyrrole monomer on the carbon surface indicated preferential filling and coverage of pores and other geometrically restricted pockets of carbon surface. On the other hand, by converting Pt into colloids in the preprecipitation method prior to their reduction, the platinum particles are forced to stay on the hybrid support; a major part of which otherwise would have been migrated into the surface pores and defect sites. Platinum particle size on these hybrid supports is 2 times higher than the catalyst prepared by polyol process. However, the electroactive surface area and mass activity are 2 times higher than that of the Pt particles prepared by polyol on hybrid material and are also significantly higher than that of the conventional electrocatalysts prepared by the polyol method. At 0.8 V, the kinetic current density (j(k)) of Pt/C-PPy-Pre obtained from the Koutecky-Levich plot is 1.5 and 2.5 times higher than that of catalysts prepared by the polyol method on PPy-coated carbon and Vulcan XC-72 carbon, respectively. Almost 210 and 160 mW cm(-2) improvement for the maximum power density, respectively with oxygen and air, was obtained with the modified system in comparison to the conventional system when the single cell evaluations were carried out at 60 degrees C with a Pt loading of 0.5 mg cm(-2) in the anode and cathode sides. This enhancement in the cell performance under the two different oxygen partial pressure conditions clearly emphasizes the improved oxygen reduction reaction (ORR) and mass-transfer characteristics of the hybrid electrode material compared to the other catalysts.